“Estudio de diferentes dosis de microorganismos benéficos en el rendimiento del cultivo de frijol (phaseolus vulgaris L.) variedad allpa poroto en Lamas” - Fababa Rios, Dan Stene (2016)
Detailed in the following work of study entitled: "Study of Different Doses of Beneficia! Organisms in the Performance of the Cultivation of Common Sean (Phaseolus vulgaris L.) Variety Allpa Sean in Lamas" whose objectives were to evaluate the effect of applications of four doses of beneficia! microorganisms in the crop yield of common bean (Paseolus vulgaris L.) using variety Allpa bean in the town of Lamas, and at the same time to determine the most appropriate dose and its influence on the increase in performance and its economic analysis of the crop. "The Pacific" farm, property of Mr. Jorge Luis Pelaez Rivera, was the place of performance of the investigation, located politically in the district and province of Lamas, San Martin department. We used the Randomized Complete Block Design (RCBD) with six treatments and four blocks. The variables used were: plant height (cm), number of pods per plant, length of the scabbard for plant, diameter of the sheath by plant, seed weight per plant (g), performance kg. ha-1, and economic analysis. The sowing was carried out on August 11 and the harvest on November 11, 2014. The results obtained indicate that the dose of 800 kg. ha-1 of beneficia! microorganisms, turned out to be the treatment that determined the greatest effect on performance and b/c of the cultivation of beans (Phaseolus vulgaris), Allpa bean variety under the edaphoclimatic conditions of the town of Lamas with 3,573.70 kg. ha-1 and with a benefit/cost with 1.18 and a net profit of S /. 267. 78, Nuevos Soles per hectare.